Living Conditions of Employees in Private Sector According to Iraqi Labor Law and Social Security- An Analytical Study in Erbil City - Dana Rahman Khidr; Sabah Ahmad Najar (Zanco Journal of Humanity Sciences)
The private sector plays a big role in the development of the economic system. In contrast to the public sector, this sector is run by individuals and companies. For this reason, the primary focus of those private institutions is based on profit. Although in the Kurdistan Region the private sector is still at the beginning of growth, it has developed a lot compared to the last two decades. The thing that drives this sector is the labor force. The labor force plays a big part of the economic system in the world, especially in the private sector. They work under certain rights and privileges that have been regulated by law. In this context, sometimes their rights are violated by the institutions where they work or by the owner of the workplace. Violation of those rights has had a big negative impact on an employee’s social and economic situation, which is considered the main subject of this study. However, the main purpose of this study is to expose employees' rights in the private sector. The descriptive analytical method has been used in explaining the rights according to Iraqi labor law No. 71 of 1987 and retirement and social security laws No. 4 of 2012. In conclusion, we have found that the Iraqi labor law provides many significant rights to employees. If they are implemented, the employee’s economic and social situation would be much better in terms of working time, day off, safety equipment, health insurance, and working conditions. Retirement and social security laws ensure permanent employment to employees and reducing the risks of losing jobs by the employees.